The Impact of Breastfeeding Duration on the Development of Normal Occlusal Features of the Primary Dentition among Baghdad Preschool Children - Munad J AL_Duliamy (College of Dentistry/ University of Baghdad, 2018)
Background: Normal occlusal features of primary dentition are crucial for normal development of the permanent dentition. Breastfeeding is an important factor for both general and dental health of children. Aim: The aim of the present study is to assess the impact of the breastfeeding duration on the prevalence of normal occlusal features of the primary dentition among preschool children in Baghdad. Materials and Methods: The sample was 630 Iraqi children (270- boys, 360 girls), aged 3-5 years selected from four kindergartens in Baghdad city. The study was carried out through questionnaire and clinical examination. Normal occlusal features were examined as the presence or absence of interincisive spaces (IS) and primate spaces (PS), terminal relationship of the primary second molar that classified as: Flush terminal (FT), mesial step (MS) and distal step (DS). The presence or absence of ideal incisor overbite was also recorded. Data were statistically analyzed using SPSS (version 21). Chi square and z test were used in data analysis. Result:s A significant relation was present between the duration of breastfeeding and the presence of: primate and interincisive spaces, flush terminal plane, mesial terminal plane and ideal incisor overbite. Conclusion Breastfeeding duration has a positive impact on the development of normal occlusal features of the primary dentition. Efforts should be taken to enhance the knowledge of the community, especially the mothers, about this impact to encourage them to practice exclusive breastfeeding for more than 12 months.